The Federal Ocean Acidification Research and Monitoring Act : H.R. 4174 : hearing before the Subcommittee on Energy and Environment, Committee on Science and Technology, House of Representatives, One Hundred Tenth Congress, second session, June 5, 2008. - United States. Congress. House. Committee on Science and Technology (2007). Subcommittee on Energy and Environment. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., U.S. G.P.O., 2008)
"Serial no. 110-106." Shipping list no.: 2009-0241-P. Includes bibliographical references. Mode of access: Internet.